2015
DOI: 10.5586/asbp.1978.022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt-stresses on the hormonal regulation of growth, photosynthesis and distribution of 14C-assimilates in bean plants

Abstract: The experiments were carried out to study the effect of salt-stresses and ABA on the growth, photosynthesis and translocation of assimilates in bean plants. It was planed to reduce the content of GA<sub>3</sub> and cytokinins and increase ABA content in salinized plants. The results show that salt-stress (NaCl and concentrated nutrient solution), reduce all the investigated processes in a different degree. NaCl-stress retarded most seriously growth of apical part and blades in contrast to 7-times c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous results showed that saline water decrease plant biomass and photosynthetic pigments due to the osmotic stress; one of the salinity effects on citrus rootstock seedlings caused by the total concentration of salt dissolved in the soil solution due to irrigation water quality, which affects the availability of free water (unbound) through physical processes (Starck and Karwowska, 1978). In the same line, salt tolerance in citrus is usually based on Cltoxicity than to Na + toxicity (Maas, 1993 andRomero-Aranda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results showed that saline water decrease plant biomass and photosynthetic pigments due to the osmotic stress; one of the salinity effects on citrus rootstock seedlings caused by the total concentration of salt dissolved in the soil solution due to irrigation water quality, which affects the availability of free water (unbound) through physical processes (Starck and Karwowska, 1978). In the same line, salt tolerance in citrus is usually based on Cltoxicity than to Na + toxicity (Maas, 1993 andRomero-Aranda et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, El-Sallami and Makary (2001) stated that salinity stress was accompanied by an increase in the content of phenolic compounds up to toxic concentration. Moreover, Stark and Karwowska (1978), working on bean plants and suggested that physiological changes occurring in plants under salt caused by hormonal imbalance. The obtained data also elucidate that Na was increased with increasing salinity levels in leaves and reverse was true for N, P and K concentration as compared with un salinized plants.…”
Section: Discussionmentioning
confidence: 99%